Geophysical Circumstances Enabling Giant Dragonfly Flight in the Carboniferous and Permian Periods - Herndon, J. Marvin (European Journal of Applied Sciences, 2025)
For more than a century there has been controversy as to the circumstances during the Carboniferous and Permian periods which made flight possible for giant dragonflies. Higher air density and elevated oxygen levels have been suggested, however, increased metabolic rates would lead to heat-exchange problems. Recently, Alan E. R. Cannell concluded from engineering investigations that higher air density, in the range 1.5-1.6 bar, would aid in thermal regulation, which would as well enhance flight aerodynamics. Contrary to plate tectonics, my new indivisible geoscience paradigm, Whole-Earth Decompression Dynamics, leads in a logical, causally-related manner to higher air density during the time giant dragonflies flourished. Even within the limitations of these simple calculations, the results suggest that during the Carboniferous and Permian periods only about half of the surface area comprising deep-ocean basins had opened.